Novelist's death loss to National Service Training Department - Borneo Post, (KK) (Borneo Post (KK), 2013)
KULIM: The death of novelist-cum-activist Pang Soon Gi who drowned on March 30 in Langkawi, is a loss to the National Service Training Department(JLKN). JLKN director general Datuk Abdul Hadi Awang Kechil said, although the 21 year old was a former PLKN trainee from the 2nd group of 7/2010 series, he had continued to serve, JLKN voluntarily and took the initiative to write a guidebook on National Service Training Programme (PLKN).